Role of Cytokines in neonatal Respiratory distress syndrome: A review article - Abdelbaseer, Khaled Abdalla; Hassan, Mohammed H.; Sayed, Mahmoud Abo alhassan; Bakri, Ali Helmi (SVU - International Journal of Medical Sciences (Online), 2023)
Background: Cytokines are non-structural proteins that have a molecular weight of less than 30 kilodaltons and are known to exert complex regulatory effects on immune response and inflammation. Biomarkers for a wide variety of diseases can be derived from cytokines, which are important mediators that regulate immune and inflammatory responses via complex networks. Macrophage migration inhibitory factor, also known as MIF, is a pleiotropic cytokine that has a structurally unique profile. It plays an important role as an upstream regulator of both innate and acquired immunity, as well as the regulation of the inflammatory response through both extracellular and intracellular processes. Research has shown that the innate cytokine known as MIF is essential for the development of the embryonic lung. They also reveal that the concentration of MIF and mutations in the MIF gene both have a role in the onset of multiple lung illnesses as well as the severity of those ailments. Objectives: The following topics will be discussed in the review article that we are writing: the potential role of cytokine (MIF) in respiratory distress syndrome (RDS) in neonates; the correlation between circulating MIF levels and RDS in neonates; genetic variations in macrophage migration inhibitory factor as a predictor of RDS in neonates and the clinical severity of RDS in neonates. Conclusion: Because of the immense promise that cytokine (MIF) holds as a biomarker in predicting the susceptibility of preterm neonates to RDS and the severity of the disease, more study has to be done on the topic.